Learning endoscopic resection in the esophagus - van Vilsteren, Frederike G. I.; Pouw, Roos E.; Alvarez Herrero, Lorenza; Bisschops, Raf; Houben, Martin; Peters, Frans T. M.; Schenk, B. E.; Weusten, Bas L. A. M.; Schoon, Erik J.; Bergman, Jacques J. G. H. M. (Endoscopy, 2015)
Background: Endoscopic resection is the cornerstone of endoscopic management of esophageal early neoplasia. However, endoscopic resection is a complex technique requiring knowledge and expertise. Our aims were to identify the most important learning points in performing endoscopic resection in a training setting and to provide information on how to improve endoscopic resection technique.Methods: Six gastroenterologists at centers with multidisciplinary expertise in upper gastrointestinal oncology participated in a structured endoscopic resection training program, consisting of four training days with lectures and hands-on training on live pigs, further one-to-one hands-on training days, and written feedback (by an expert) on videos of unsupervised endoscopic resection procedures. The first 20 endoscopic resections of each participant were prospectively registered. Ninety learning points were independently identified by participants using a standardized questionnaire and by an expert providing written feedback on 33 unsupervised endoscopic resection videos. Three expert endoscopists selected and ranked the most important learning points in a consensus meeting. Results. The top 10 tips (illustrated by unique videos of three perforations) were: (1) allow time for inspection and use a high-definition endoscope; (2) create a preprocedural plan by placing electrocoagulation markings; (3) know the management of bleeding; (4) optimize the endoscopic view by repeatedly cleaning out stomach and target area; (5) use a therapeutic endoscope during resection; (6) always perform a test suction; (7) keep instruments close to the tip; (8) lift edges in piecemeal endoscopic cap resections; (9) know the management of perforation; (10) pin specimens down.Conclusions: This study summarized the most important learning points for performing endoscopic resection encountered during a structured endoscopic resection training program.